A multi-strategy enhanced African vultures optimization algorithm for global optimization problems. Issue 1 (1st February 2023) - Zheng, Rong; Hussien, Abdelazim G; Qaddoura, Raneem; Jia, Heming; Abualigah, Laith; Wang, Shuang; Saber, Abeer
Abstract: The African vultures optimization algorithm (AVOA) is a recently proposed metaheuristic inspired by the African vultures' behaviors. Though the basic AVOA performs very well for most optimization problems, it still suffers from the shortcomings of slow convergence rate and local optimal stagnation when solving complex optimization tasks. Therefore, this study introduces a modified version named enhanced AVOA (EAVOA). The proposed EAVOA uses three different techniques namely representative vulture selection strategy, rotating flight strategy, and selecting accumulation mechanism, respectively, which are developed based on the basic AVOA. The representative vulture selection strategy strikes a good balance between global and local searches. The rotating flight strategy and selecting accumulation mechanism are utilized to improve the quality of the solution. The performance of EAVOA is validated on 23 classical benchmark functions with various types and dimensions and compared to those of nine other state-of-the-art methods according to numerical results and convergence curves. In addition, three real-world engineering design optimization problems are adopted to evaluate the practical applicability of EAVOA. Furthermore, EAVOA has been applied to classify multi-layer perception using XOR and cancer datasets. The experimental results clearly show that the EAVOA has superiority over other methods. Graphical Abstract: